(untitled) (International Seven Journal of Health Research, 2024)
Hemorrhagic syndromes in the first half of pregnancy comprise potentially serious clinical conditions, including abortion, ectopic pregnancy and hydatidiform mole. Miscarriage, defined as termination of pregnancy before 20 weeks or with a fetal weight of less than 500 g, is the most common cause, with multifactorial etiologies such as genetic alterations and maternal factors. Ectopic pregnancy occurs when the embryo implants itself outside the uterine cavity, often in the fallopian tubes, and is associated with severe abdominal pain and the risk of rupture with bleeding. Hydatidiform mole, a gestational trophoblastic disease, is characterized by abnormal trophoblast proliferation and pathological placental development. Diagnosis is based on clinical history, ultrasound and beta-hCG levels. Management depends on the etiology and may include curettage, laparoscopy or chemotherapy in the case of hydatidiform mole. Early identification and appropriate treatment are essential to reduce maternal morbidity and mortality.